Validation of a novel method for localization of parathyroid adenomas using SPECT/CT - Rachelle A. LeBlanc; Andre Isaac; Jonathan Abele; Vincent L. Biron; David W. J. Côté; Matthew Hearn; Daniel A. O’Connell; Hadi Seikaly; Jeffrey R. Harris (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background Accurate localization of parathyroid adenomas is of critical importance in surgical planning for minimally invasive parathyroidectomy. SPECT/CT is considered the investigation of choice but has limitations regarding localization of superior versus inferior adenomas. We proposed a novel method for localization using SPECT/CT by determining the anterior-posterior relationship of the adenoma to a horizontal line in the coronal plane through the tracheoesophageal groove. Our objective was to determine the accuracy, validity, and inter-rater reliability of this method. Method This was a retrospective review of patients who underwent parathyroidectomy for a single adenoma between 2010-2017. SPECT/CT images were reviewed by two staff Otolaryngologists, a Radiologist, an Otolaryngology fellow and Otolaryngology resident. Results were compared using intra-operative report as the gold standard. Overall accuracy in determining superior/inferior and right/left adenomas was calculated, as well as Cohen's Kappa to determine agreement with operative report and inter-rater reliability. The performance was compared to that of the original radiology report. Results One hundred thirty patients met criteria and were included. Our method correctly identified the location of the adenoma in terms of both side and superior/inferior position in 80.4% [76 - 84%] of patients, which considerably outperformed the original radiology report at 48.5% [4-78%] accuracy. The agreement level between our method and operative report was high (Kappa=0.717 [0.691-0.743]), as was the inter-rater reliability (Kappa=0.706 [0.674-0.738]). Conclusion We report a novel method for localization of parathyroid adenomas using SPECT/CT which outperforms standard radiology reporting. This tool can be used by surgeons and radiologists to better inform and plan for minimally invasive parathyroidectomy.